Transient gibberellin application promotes Arabidopsis thaliana hypocotyl cell elongation without maintaining transverse orientation of microtubules on the outer tangential wall of epidermal cells - Sauret-Güeto, S; Calder, G; Harberd, N (2012)
The phytohormone gibberellin (GA) promotes plant growth by stimulating cellular expansion. Whilst it is known that GA acts by opposing the growth-repressing effects of DELLA proteins, it is not known how these events promote cellular expansion. Here we present a time-lapse analysis of the effects of a single pulse of GA on the growth of Arabidopsis hypocotyls. Our analyses permit kinetic resolution of the transient growth effects of GA on expanding cells. We show that pulsed application of GA to the relatively slowly growing cells of the unexpanded light-grown Arabidopsis hypocotyl results in a transient burst of anisotropic cellular growth. This burst, and the subsequent restoration of initial cellular elongation rates, occurred respectively following the degradation and subsequent reappearance of a GFP-tagged DELLA (GFP-RGA). In addition, we used a GFP-tagged α-tubulin 6 (GFP-TUA6) to visualise the behaviour of microtubules (MTs) on the outer tangential wall (OTW) of epidermal cells. In contrast to some current hypotheses concerning the effect of GA on MTs, we show that the GA-induced boost of hypocotyl cell elongation rate is not dependent upon the maintenance of transverse orientation of the OTW MTs. This confirms that transverse alignment of outer face MTs is not necessary to maintain rapid elongation rates of light-grown hypocotyls. Together with future studies on MT dynamics in other faces of epidermal cells and in cells deeper within the hypocotyl, our observations advance understanding of the mechanisms by which GA promotes plant cell and organ growth. © 2011 Blackwell Publishing Ltd.